2016
DOI: 10.1007/s11695-016-2189-x
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction in Bariatric Surgery Candidates: Prevalence and Risk Factors

Abstract: Systematic screening for and treatment of FA symptoms before obesity surgery is critical because FA symptoms are prevalent and associated with poorer psychosocial outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 14 publications
9
42
2
1
Order By: Relevance
“…In our group of non-selected participants with obesity, the frequency of BE and FA positive scores were, respectively, 21.2 and 23.7% figures similar with previous reports [37]. However, higher figures for BE have been also reported 36.2-42.4% [38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our group of non-selected participants with obesity, the frequency of BE and FA positive scores were, respectively, 21.2 and 23.7% figures similar with previous reports [37]. However, higher figures for BE have been also reported 36.2-42.4% [38].…”
Section: Discussionsupporting
confidence: 91%
“…This association has been already reported [37]; therefore, both conditions might share common physiopathological pathways [41]. Nevertheless, OC eating may have different features.…”
Section: Discussionsupporting
confidence: 67%
“…In accordance with our hypothesis, the prevalence of probable eating, anxiety, and major depressive disorders in the present sample was as high as expected based on literature (Baldofski et al, ; Brunault et al, ; Brunault et al, ; Ivezaj et al, ; Koball et al, ; Meule et al, ; Meule et al, ; Miller‐Matero et al, ; Ouellette et al, ). The current results further resemble findings from previous studies in bariatric surgery patients that indicate that those with FA are more likely than those without FA to exhibit eating disorder and anxiety and depressive disorder symptoms (Brunault et al, ; Koball et al, ; Meule et al, ; Miller‐Matero et al, ). Last but not least, the proportion of patients being at risk for buying disorder in the present preoperative sample (17.3%) exceeded population‐based prevalence estimates (4.8%, Müller et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study was identified with a high proportion of males (92%, in a veteran study) (62) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) .…”
Section: Description Of Included Studiesmentioning
confidence: 99%